Genotype and phenotype correlation in von Hippel–Lindau disease based on alteration of the HIF-α binding site in VHL protein. (October 2018) - Liu, Sheng-Jie; Wang, Jiang-Yi; Peng, Shuang-He; Li, Teng; Ning, Xiang-Hui; Hong, Bao-An; Liu, Jia-Yuan; Wu, Peng-Jie; Zhou, Bo-Wen; Zhou, Jing-Cheng; Qi, Nie-Nie; Peng, Xiang; et al.
Abstract Purpose Von Hippel–Lindau (VHL) disease is a rare hereditary cancer syndrome that reduces life expectancy. We aimed to construct a more valuable genotype–phenotype correlation based on alterations in VHL protein (pVHL). Methods VHL patients (n = 339) were recruited and grouped based on mutation types: HIF-α binding site missense (HM) mutations, non-HIF-α binding site missense (nHM) mutations, and truncating (TR) mutations. Age-related risks of VHL-associated tumors and patient survival were compared. Results Missense mutations conferred an increased risk of pheochromocytoma (HR = 1.854, p = 0.047) compared with truncating mutations. The risk of pheochromocytoma was lower in the HM group than in the nHM group (HR = 0.298, p = 0.003) but was similar between HM and TR groups (HR = 0.901, p = 0.810). Patients in the nHM group had a higher risk of pheochromocytoma (HR = 3.447, p < 0.001) and lower risks of central nervous system hemangioblastoma (CHB) (HR = 0.700, p = 0.045), renal cell carcinoma (HR = 0.610, p = 0.024), and pancreatic tumor (HR = 0.382, p < 0.001) than those in the combined HM and TR (HMTR) group. Moreover, nHM mutations were independently associated with better overall survival (HR = 0.345, p = 0.005) and CHB-specific survival (HR = 0.129, p = 0.005) than HMTR mutations. Conclusion The modified genotype–phenotype correlation linksVHL gene mutation, substrate binding site, and phenotypic diversity (penetrance and survival), and provides more accurate information for genetic counseling and pathogenesis studies.